Dermal exposure to pesticides and health symptoms of paddy farmers in Seberang Perak, Malaysia - Mohammad, Khadijah (2019)
Pesticides are hazardous to the global public health since numerous studies had identified several problems related to occupational diseases, caused by the higher pesticide usage in the agricultural sectors. A cross-sectional study design was conducted on 179 paddy farmers in Seberang Perak, Malaysia. The aim of this study was to estimate actual dermal exposure to pesticides among paddy farmers using Dermal Exposure Assessment Method (DREAM). Apart from that, this study aimed to determine the socio-demographic, characteristics of pesticides, use of Personal Protective Equipment (PPE), duration of exposure, the prevalence of health symptoms experienced by paddy farmers, comparison between activities, use of PPE, and pesticides physical form with actual dermal exposure to pesticides, and relationship between socio-demographic characteristic, use of PPE and duration of exposure with prevalence of health symptoms experienced by paddy farmers. These findings indicated no greater than moderate levels of risks during both activities. On the average, estimated potential dermal exposure (SkinW-PTASK) resulted higher than the actual dermal exposure (SkinW-ATASK) for both mixing/loading and spraying activities. Conversely, the SkinW-ATASK value of spraying was higher than that of the mixing/loading activities. The independent t-tests analysis showed there were a significant difference (p < 0.001) between the actual dermal exposure and activities, use of PPE during spraying activities, and pesticides physical form during the mixing/loading activities. Besides, the lower parts of the body contributed the most to the high SkinWATASK value during spraying, along with more than 50% prevalence of skin irritation. In contrast, hands received the greatest exposure to pesticides during the mixing/loading activities, as a result from 100% non-usage of gloves. Apart from the actual dermal exposure, findings revealed several factors contributed to the health status of the paddy farmers, which includes the use of PPE, duration of exposure, and specific sociodemographic characteristics. A chi-square test analysis showed a significant relationship between health symptoms and the use of PPE for headache, dizziness, numbness, finger tingling, blurring of vision, skin rashes, skin irritation, and eye itchiness (p < 0.05). Moreover, a chi-square test analysis also showed a significant relationship between skin irritation on hands/wrists and the use of PPE (p < 0.05). Finally, this study revealed that there was statistically significant relationship (p < 0.05) between general health symptoms and the employment years, education level as well as duration of exposure. From those findings, it can be concluded that actual dermal exposure and the health status of the paddy farmers were highly dependent on the activities, use of PPE, pesticides physical form, sociodemographic characteristics, and duration of exposure. Due to the limitation of this study as there was no direct quantitative data taken, DREAM could serve as an alternative method in risk assessment.